The importance of the agricultural sector to the Malaysian economy: analyses of inter-industry linkages - Saari, Mohd Yusof; Alias, Emmy Farha; Abdullah Chik, Norlaila (Universiti Putra Malaysia Press, 2013)
This paper assesses the importance of the agricultural sector to the economic growth in Malaysia. A hypothetical extraction method was used to quantify the relative strength of backward and forward linkages of the agricultural sector. For empirical analyses, we ran an extended input-output table that takes into account detailed agricultural sub-sectors. Findings suggested that the agricultural sector contributes mainly through forward linkages, implying that the output of this sector is demanded larger by other sectors, in particular the manufacturing sector as their input. Large-scale oil palm (estate and smallholdings) should be highlighted for growth policies due to strong pull effects on the rest of the economic sector.